Multi-alloy magnet with high comprehensive performance and preparation method thereof
By mixing the NdaM100-a-b-cFebBc alloy with high magneto crystal anisotropy field with low-cost (Nd1-xREx)aM100-a-b-cFebBc alloy and compounding it with the hard auxiliary alloy Al-X-B to form a double-main phase alloy, the problem of insufficient mechanical properties of Nd-Fe-B magnet under high magnetic properties is solved, and the excellent magnetic properties and mechanical properties of the magnet are improved.
Patent Information
- Application Number
- CN202411716071.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing Nd-Fe-B magnets are difficult to ensure mechanical properties while improving magnetic properties. Especially under high magnetic properties, the mechanical properties of the magnets are insufficient, resulting in crack expansion during fracture and affecting performance.
By mixing the NdaM100-a-b-cFebBc alloy with a high magneto-crystal anisotropy field with a low-cost (Nd1-xREx)aM100-a-b-cFebBc alloy, and recombining it with the hard auxiliary alloy Al-X-B to form a double-main phase alloy. The concentration gradient of rare earth elements promotes the uniform distribution of Al-X-B at the grain boundary, enhances the capillary effect at the grain boundary, inhibits abnormal growth of grains, and improves the mechanical properties of the magnet.
The excellent magnetic and mechanical properties of Nd-Fe-B magnets have been improved. Through the homogenization distribution of Al-X-B and the grain refinement effect, the crack expansion of the magnets during fracture is suppressed, and the comprehensive performance of the magnets is significantly improved.
Smart Images

Figure CN119601332A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth permanent magnet materials, and in particular relates to a multi-alloy high-comprehensive-performance magnet and a preparation method thereof. Background Art
[0002] Sintered NdFeB magnets are widely used in permanent magnetic levitation rails, aerospace, new energy vehicles, wind power generation and other fields due to their excellent magnetic properties. The requirements for the mechanical properties of magnets are gradually increasing, but due to the contradiction between magnetocrystalline anisotropy and mechanical anisotropy, it is difficult to ensure good mechanical properties while maintaining high magnetic properties.
[0003] With the diversification of the service conditions of Nd-Fe-B magnets, the demand for high-comprehensive-performance magnets with excellent magnetic and mechanical properties is gradually increasing. Patents CN102800454A, CN103545079A, CN105321644A, and CN106357175A mention that dual-phase sintered magnets prepared by traditional sintering technology can weaken the magnetic dilution effect of high-abundance rare earths; Patents CN117144201A, CN115821119A, and CN110184503A mention that refiners are often used in aluminum alloy materials to achieve the purpose of grain refinement, and the grain refinement effect has a very obvious effect on the microstructure of Nd-Fe-B magnets, and has a positive promoting effect on the magnetic properties and mechanical properties of Nd-Fe-B magnets. Common studies have achieved grain refinement by adding high-melting-point elements such as Zr and Ti to single-phase magnetic powder, and these high-melting-point elements tend to aggregate at grain boundaries, limiting the grain refinement effect of high-melting-point elements. However, there is little description of multi-alloy sintering technology that adds hard auxiliary alloy Al-XB powder to achieve grain refinement and achieves homogeneous distribution of hard auxiliary alloy Al-XB powder through a dual-main phase process, where X is one or more of Ti, Hf, Zr, and Nb elements. Summary of the invention
[0004] The purpose of the present invention is to provide a multi-alloy high-comprehensive performance magnet and a preparation technology thereof. Two main phase magnetic powders are mixed with Al-XB hard auxiliary alloy powders and pressed, wherein X is one or more of Ti, Hf, Zr, and Nb elements. The purpose of the present invention is to enhance the capillary action of the grain boundary and promote the homogenized distribution of the high-melting-point Al-XB hard phase at the grain boundary through the interdiffusion of rare earth elements formed by the main phase concentration gradient, enhance the grain refinement effect of the Al-XB hard phase and the suppression effect of crack propagation during the magnet fracture process, and prepare a multi-alloy high-comprehensive performance magnet with excellent magnetic properties and mechanical properties.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A multi-alloy high comprehensive performance magnet, composed of a chemical formula mass percentage of Nd with a high magnetocrystalline anisotropy field a M 100-a-b-c Fe b B c The chemical formula mass percentage of alloy and low cost is (Nd 1-x RE x ) a M 100-a-b-c Fe b B c The dual-phase alloy formed by the alloy is composited with the hard auxiliary alloy Al-XB, wherein 26≤a≤34, 60≤b≤68, 0.9≤c≤1.1, 0<x≤90, RE is one or more of the high-abundance rare earth elements La, Ce, and Y, M is one or more of the elements Zn, Ga, Co, Cu, Nb, Sn, and Mn, and X is one or more of the elements Ti, Hf, Zr, and Nb; the mass ratio of the dual-phase alloy to the hard auxiliary alloy is 1:0.002-2.
[0007] Preferably, the mass ratio of the dual-main-phase alloy to the hard auxiliary alloy is 1:0.002-0.004.
[0008] Preferably, the chemical formula mass percentage of the hard alloy Al—XB is AlX5B.
[0009] Considering the cost and magnetic properties, in the dual-phase alloy, the Nd a M 100-a-b-c Fe b B c Alloy with (Nd 1-x RE x ) a M 100-a-b-c Fe b B c The mass ratio of the alloy is preferably 1:0.5-4, preferably 1:1.
[0010] The present invention adopts conventional Nd a M 100-a-b-c Fe b B c The main phase alloy contains high abundance rare earth elements (Nd 1-x RE x ) a M 100-a-b-c Fe b B cThe main phase alloy and nano-hard auxiliary alloy Al-XB powder are mixed with each other, the purpose of which is: (1) using high-abundance rare earth RE to partially replace Nd in Nd-Fe-B magnets, increasing the amount of high-abundance rare earth in magnets, reducing the manufacturing cost of magnets, and alleviating the problems of resource waste and environmental pollution caused by the long-term accumulation of high-abundance rare earths; (2) forming two alloy main phases with significant differences in magnetocrystalline anisotropy fields, promoting the uniform distribution of Al-XB at the grain boundary through the rare earth element migration between Nd and high-abundance rare earth elements between the two main phases, so that the expansion of cracks during intergranular fracture during the fracture process of the magnet is suppressed, and the mechanical properties of the magnet are improved. The high-melting point Al-XB's inhibition of abnormal grain growth can also effectively refine the main phase grains, optimize the grain boundaries, and inhibit the coupling of neighboring grains, so that the permanent magnets jointly regulated by Al-XB addition and dual main phase process show better comprehensive performance.
[0011] The present invention also provides a method for preparing the above-mentioned multi-alloy high comprehensive performance magnet, comprising the following steps:
[0012] (1) Preparation of raw materials: Preparation of Nd a M 100-a-b-c Fe b B c and (Nd 1-x RE x ) a M 100-a-b-c Fe b B c Alloy raw materials;
[0013] (2) Rapid solidification belt: The configured raw materials are placed in a smelting rapid solidification furnace to obtain Nd a M 100-a-b-c Fe b B c and (Nd 1-x RE x ) a M 100-a-b-c Fe b B c Alloy quick-setting sheet;
[0014] (3) Hydrogen crushing: The two alloy quick-setting sheets are placed in hydrogen crushing tanks respectively, and coarse-grained alloy powders are obtained through hydrogen absorption and dehydrogenation reactions;
[0015] (4) Jet milling: The hydrogen powder obtained in step (3) is crushed under nitrogen and a classifying wheel is used to obtain alloy powder with a particle size of 2.6-3.1 μm;
[0016] (5) Mixed powder pressing: The particle size of the hard auxiliary alloy Al-XB powder needs to be controlled within the range of 10-500 nm, and the mass percentage of the added powder is 0.002-2%. The two main phase magnetic powders and the hard auxiliary alloy Al-XB powder are mixed in a powder mixer under a protective atmosphere for 10-20 minutes and pressed into blocks, which are then sealed in a bag and cold isostatically pressed at a pressure of 150-200 MPa and a pressing time of 0.01-5 minutes.
[0017] (6) Sintering: Sinter the block to obtain a fully dense Nd2Fe2O3 with high magnetocrystalline anisotropy field. 14 B main phase and low-cost (Nd,RE)2Fe 14 Composite sintered magnet with B main phase and hard auxiliary alloy phase.
[0018] Preferably, the method for preparing the alloy quick-setting sheet in step (2) is as follows: evacuating the melting quick-setting furnace, introducing argon gas after heating the furnace, heating the crucible with medium frequency current to a temperature of 1400-1600°C for refining, pouring the alloy liquid into a tundish, and guiding it to a cold roller for cooling and quick-setting into a quick-setting sheet. The cold roller rotates at a speed of 1.15-1.5 m / s, the quick-setting sheet has a thickness of 0.25-0.4 mm, and the copper roller cooling water temperature is 18-25°C.
[0019] Preferably, the hydrogen absorption and dehydrogenation reaction method in step (3) is: vacuumizing the hydrogen tank, absorbing hydrogen at room temperature at a hydrogen pressure of 0.5-0.7 MPa for 1.2-2.0 h, and dehydrogenating at 480-520° C. for 2.5-3.5 h.
[0020] Preferably, in the jet milling process in step (4), the rotation speed of the classifying wheel is 4300-4500 r / min.
[0021] The present invention utilizes powder metallurgy technology to prepare Nd a M 100-a-b-c Fe b B c and (Nd 1-x RE x ) a M 100-a-b-c Fe b B cTwo different types of quick-setting sheets are prepared under argon protection by hydrogen decomposition and gas flow grinding and uniformly mixed with hard alloy Al-XB to obtain mixed multi-alloy magnetic powder. After liquid phase sintering, sintered magnets with two types of main phases are obtained. The two alloy main phases have significant differences in magnetocrystalline anisotropy fields. The concentration gradient formed by the concentration difference of Nd and high-abundance rare earth elements in the two alloys promotes the uniform distribution of Al-XB at the grain boundary, inhibits the extension of intergranular fracture cracks during the fracture process, and the high-melting point Al-XB inhibits abnormal grain growth and also acts on the main phase grains, optimizes the grain boundaries, and inhibits the coupling of neighboring grains, so that the permanent magnet with dual regulation of hard auxiliary alloy Al-XB addition and dual main phase process shows more excellent comprehensive performance. The density of sintered magnets, the uniformity of mixed powders, and the particle size control of hard auxiliary alloy Al-XB are the key to the preparation of high comprehensive performance magnets.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) Using high-abundance rare earth RE to partially replace Nd in Nd-Fe-B magnets increases the amount of high-abundance rare earth in the magnet, reduces the manufacturing cost of the magnet, and alleviates the problems of resource waste and environmental pollution caused by the long-term backlog of high-abundance rare earth;
[0024] (2) Two alloy main phases with significantly different magnetocrystalline anisotropy fields are formed. The concentration gradient formed by the concentration difference of Nd and high-abundance rare earth elements in the two alloys promotes the uniform distribution of Al-XB at the grain boundaries, inhibits the extension of intergranular fracture cracks during the fracture process, and the high-melting point Al-XB inhibits abnormal grain growth and also acts in the opposite direction on the main phase grains, optimizing the grain boundaries and inhibiting the coupling effect of neighboring grains, so that the permanent magnet with dual control of hard auxiliary alloy Al-XB addition and multi-alloy process exhibits more excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the enrichment diagram of Al-XB (black needles) in a single-phase magnet;
[0026] Figure 2 Schematic diagram of the process in which rare earth elements diffuse mutually between the main phases of a dual-main-phase magnet to form a core-shell structure while promoting the homogenization of Al-XB. DETAILED DESCRIPTION
[0027] The following is a further detailed description in conjunction with specific implementation modes. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.
[0028] Example 1
[0029] (1) Prepare the main phase A:Nd by mass percentage 31 Ga0.1 Co 0.3 Cu 0.2 B 0.93 Fe 67.47 and main phase B:(Nd 0.7 Ce 0.3 ) 31 Ga 0.1 Co 0.3 Cu 0.2 B 0.93 Fe 67.47 .
[0030] (2) Place the configured main phase A and main phase B into the melting and quick solidification furnace respectively and evacuate to 5×10 -3 Pa, after heating to 400℃, high-purity argon (argon volume content is 99.999%) is introduced into the furnace, the crucible temperature is heated to 1500℃ by medium frequency current for refining for 4min, the alloy liquid is poured into the tundish, and the liquid is guided to the cold roller for cooling and rapid solidification into a rapid solidification sheet. The speed of the cold roller is 1.3m / s, and the thickness of the rapid solidification sheet is 0.28mm;
[0031] (3) Place the alloy quick-solidification sheets into hydrogen rupture tanks and evacuate to 1×10 -3 Pa, absorbing hydrogen at room temperature for 1.5 h at a hydrogen pressure of 0.6 MPa, and dehydrogenating at 500 ° C for 3 h, and obtaining a coarse-grained alloy powder after hydrogen absorption and dehydrogenation reactions;
[0032] (4) crushing the hydrogen powder under high-purity nitrogen (nitrogen volume content of 99.999%), passing through a jet mill with a separation wheel speed of 4300 r / min, to obtain an average particle size of 2.8 μm;
[0033] (5) The main phase A and the main phase B are mixed in a mass ratio of 1:1, and the magnetic powder and the hard auxiliary alloy AlTi5B (atomic ratio) powder with a particle size of 100 nm are mixed in a mass ratio of 1:0.0023 under vacuum drying, and pressed into a block of 25×25×25 mm under the protection of high-purity nitrogen, and then isostatically pressed with a pressing pressure of 200 MPa and a holding time of 5 min;
[0034] (6) Place the block into a graphite box, place it in a tubular sintering furnace, and evacuate to 1×10 -3 Pa, sintered at elevated temperature to obtain dense (Nd 0.85 Ce 0.15 ) 31 Ti 0.2 Ga 0.1 Co 0.3 Al 0.02 Cu 0.2 B 0.94 Fe 67.24 Multi-alloy magnets.
[0035] (7) For comparison purposes, the same composition of single-phase magnetic powder (Nd 0.85 Ce 0.15 ) 31 Ga 0.1 Co 0.3 Cu 0.2 B 0.93 Fe 67.47 The powder was mixed with AlTi5B powder, a hard auxiliary alloy with a particle size of 100 nm, and a single main phase magnet was obtained through the same preparation process.
[0036] The upper sintered magnet was made into a cylindrical sample with a diameter of 10 mm and a height of 10 mm and a rectangular sample of 5×6×22 mm by wire cutting and internal cutting, respectively. The magnetic properties and bending strength were tested using a NIM-2000HF rare earth permanent magnet measuring device and a universal testing machine. The properties are shown in Table 1.
[0037] Example 2
[0038] (1) Prepare the main phase A:Nd by mass percentage 31 Ga 0.1 Co 0.3 Cu 0.2 B 0.93 Fe 67.47 and main phase B:(Nd 0.7 Ce 0.3 ) 31 Ga 0.1 Co 0.3 Cu 0.2 B 0.93 Fe 67.47 .
[0039] (2) Place the configured main phase A and main phase B into the melting and quick solidification furnace respectively and evacuate to 5×10 -3 Pa, after heating to 400℃, high-purity argon is introduced into the furnace, the crucible temperature is heated to 1500℃ by medium frequency current and refined for 4min, the alloy liquid is poured into the tundish, and guided to the cold roller for cooling and rapid solidification into a rapid solidification sheet, the speed of the cold roller is 1.3m / s, and the thickness of the rapid solidification sheet is 0.28mm;
[0040] (3) Place the alloy quick-solidification sheets into hydrogen rupture tanks and evacuate to 1×10 -3 Pa, absorbing hydrogen at room temperature for 1.5 h at a hydrogen pressure of 0.6 MPa, and dehydrogenating at 500 ° C for 3 h, and obtaining a coarse-grained alloy powder after hydrogen absorption and dehydrogenation reactions;
[0041] (4) The hydrogen was crushed into powder under high-purity nitrogen and passed through a jet mill with a separation wheel speed of 4300 r / min to obtain an average particle size of 2.8 μm;
[0042] (5) The main phase A and the main phase B were mixed in a mass ratio of 1:1, and the magnetic powder and the hard auxiliary alloy AlZr5B (atomic ratio) powder with a particle size of 100 nm were mixed in a ratio of 1:0.0025 under vacuum drying and pressed into a 25×25×25 mm block under the protection of high-purity nitrogen, and then isostatically pressed with a pressing pressure of 200 MPa and a holding time of 5 min.
[0043] (6) Place the block into a graphite box, place it in a tubular sintering furnace, and evacuate to 1×10 -3 Pa, sintered at elevated temperature to obtain dense (Nd 0.85 Ce 0.15 ) 31 Zr 0.21 Ga 0.1 Co 0.3 Cu 0.2 Al 0..01 B 0.95 Fe 67.23 Alloy magnets.
[0044] (7) For comparison purposes, the same composition of single-phase magnetic powder (Nd 0.85 Ce 0.15 ) 31 Ga 0.1 Co 0.3 Cu 0.2 B 0.93 Fe 67.47 The powder was mixed with AlZr5B powder, a hard auxiliary alloy with a particle size of 100 nm, and a single main phase magnet was obtained through the same preparation process.
[0045] The upper sintered magnet was made into a cylindrical sample with a diameter of 10 mm and a height of 10 mm and a rectangular sample of 5×6×22 mm by wire cutting and internal cutting, respectively. The magnetic properties and bending strength were tested using a NIM-2000HF rare earth permanent magnet measuring device and a universal testing machine. The properties are shown in Table 1.
[0046] Example 3
[0047] (1) Prepare the main phase A:Nd by mass percentage 31 Ga 0.1 Co 0.3 Cu 0.2 B 0.93 Fe 67.47 and main phase B:(Nd 0.7 Ce 0.3 ) 31 Ga 0.1 Co 0.3 Cu 0.2 B 0.93 Fe 67.47 .
[0048] (2) Place the configured main phase A and main phase B into the melting and quick solidification furnace respectively and evacuate to 5×10 -3 Pa, after heating to 400℃, high-purity argon is introduced into the furnace, and the crucible temperature is heated to 1500℃ by medium frequency current for refining for 4 minutes. The alloy liquid is poured into the tundish and guided to the cold roller for cooling and rapid solidification into a rapid solidification sheet. The speed of the cold roller is 1.3m / s, and the thickness of the rapid solidification sheet is 0.28mm;
[0049] (3) Place the alloy quick-solidification sheets into hydrogen rupture tanks and evacuate to 1×10 -3 Pa, absorbing hydrogen at room temperature for 1.5 h at a hydrogen pressure of 0.6 MPa, and dehydrogenating at 500 ° C for 3 h, and obtaining a coarse-grained alloy powder after hydrogen absorption and dehydrogenation reactions;
[0050] (4) The hydrogen was crushed into powder under high-purity nitrogen and passed through a jet mill with a separation wheel speed of 4300 r / min to obtain an average particle size of 2.8 μm;
[0051] (5) The main phase A and the main phase B were mixed in a mass ratio of 1:1, and the magnetic powder and the hard auxiliary alloy AlHf5B (atomic ratio) powder with a particle size of 100 nm were mixed in a ratio of 1:0.0036 under vacuum drying and pressed into a 25×25×25 mm block under the protection of high-purity nitrogen, and then isostatically pressed with a pressing pressure of 200 MPa and a holding time of 5 min.
[0052] (6) Place the block into a graphite box, place it in a tubular sintering furnace, and evacuate to 1×10 -3 Pa, sintered at elevated temperature to obtain dense (Nd 0.85 Ce 0.15 ) 31 Hf 0.31 Ga 0.1 Co 0.3 Cu 0.2 Al 0.01 B 0.96 Fe 67.12 Alloy magnets.
[0053] (7) For comparison purposes, the same composition of single-phase magnetic powder (Nd 0.85 Ce 0.15 ) 31 Ga 0.1 Co 0.3 Cu 0.2 B 0.93 Fe 67.47 The powder was mixed with AlHf5B powder, a hard auxiliary alloy with a particle size of 100 nm, and a single main phase magnet was obtained through the same preparation process.
[0054] The upper sintered magnet was made into a cylindrical sample with a diameter of 10 mm and a height of 10 mm and a rectangular sample of 5×6×22 mm by wire cutting and internal cutting, respectively. The magnetic properties and bending strength were tested using a NIM-2000HF rare earth permanent magnet measuring device and a universal testing machine. The properties are shown in Table 1.
[0055] Table 1 Magnetic properties and flexural strength of magnets prepared by different methods (SMP is a single-phase process, DMP is a dual-phase process)
[0056]
[0057]
[0058] The results of the examples show that the magnets prepared by adding Al-XB and dual-phase dual-control have better comprehensive performance than the single-phase process. The reasons are as follows Figure 1 and Figure 2 As shown, Figure 1 The SMP single-phase process shows that Al XB (black needles) are enriched in the single-phase magnet. Figure 2 In the DMP dual-phase process, the rare earth elements between the main phases of the dual-phase magnet diffuse into each other to form a core-shell structure while promoting the homogenization of Al-XB.
[0059] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the protection scope of the present invention. Any changes and modifications made by technicians familiar with the technology without departing from the concept and scope of the present invention shall fall within the protection scope of the present invention.
Claims
1. A multi-alloy high comprehensive performance magnet, characterized by: The chemical formula mass percentage is Nd a M 100-a-b- c Fe b B c Alloy and (Nd 1-x RE x ) a M 100-a-b-c Fe b B c The dual-phase alloy formed by the alloy is composited with the hard auxiliary alloy Al-XB, wherein 26≤a≤34, 60≤b≤68, 0.9≤c≤1.1, 0<x≤90, RE is one or more of the high-abundance rare earth elements La, Ce, and Y, M is one or more of the elements Zn, Ga, Co, Cu, Nb, Sn, and Mn, and X is one or more of the elements Ti, Hf, Zr, and Nb; the mass ratio of the dual-phase alloy to the hard auxiliary alloy is 1:0.002-2.
2. The multi-alloy high comprehensive performance magnet according to claim 1, characterized in that: The mass ratio of the dual-phase alloy to the hard auxiliary alloy is 1:0.002-0.
004.
3. The multi-alloy high comprehensive performance magnet according to claim 1, characterized in that: The Nd a M 100-a-b-c Fe b B c Alloy with (Nd 1-x RE x ) a M 100-a-b-c Fe b B c The mass ratio of the alloy is 1:0.5-4.
4. The multi-alloy high comprehensive performance magnet according to claim 1, characterized in that: The atomic ratio of each element of the hard auxiliary alloy Al-XB is AlX5B.
5. A method for preparing a multi-alloy high comprehensive performance magnet as claimed in any one of claims 1 to 4, comprising the following steps: (1) Preparation of raw materials: Preparation of Nd a M 100-a-b-c Fe b B c and (Nd 1-x RE x ) a M 100-a-b-c Fe b B c Alloy raw materials; (2) Rapid solidification belt: The configured raw materials are placed in a smelting rapid solidification furnace to obtain Nd a M 100-a-b-c Fe b B c and (Nd 1- x RE x ) a M 100-a-b-c Fe b B c Alloy quick-setting sheet; (3) Hydrogen crushing: The two alloy quick-solidification sheets are placed in hydrogen crushing tanks respectively, and coarse-grained alloy powders are obtained through hydrogen absorption and dehydrogenation reactions; (4) Jet milling: The hydrogen-crushed powder obtained in step (3) is subjected to nitrogen protection and a classifying wheel is used to obtain alloy powder with a particle size of 2.6-3.1 μm; (5) Mixed powder pressing: The particle size of the hard auxiliary alloy Al-XB powder is controlled to be 10-500nm, and the mass percentage of the added powder is 0.002-2%. The two main phase magnetic powders and the hard auxiliary alloy Al-XB powder are mixed in a powder mixer under a protective atmosphere for 10-20min and pressed into blocks, and then sealed in a bag for cold isostatic pressing, with a pressing pressure of 150-200MPa and a pressing time of 0.01-5min. (6) Sintering: Sinter the block to obtain a dense Nd2Fe 14 B main phase and low-cost (Nd,RE)2Fe 14 Composite sintered magnet with B main phase and hard auxiliary alloy phase.
6. The preparation method according to claim 5, characterized in that: The method for preparing the alloy quick-setting sheet in step (2) is as follows: evacuating the melting quick-setting furnace, introducing argon gas after heating the furnace, heating the crucible to 1400-1600° C. with a medium frequency current for refining, pouring the alloy liquid into a tundish, and guiding it to a cold roller for cooling and quick-setting into a quick-setting sheet. The cold roller rotates at a speed of 1.15-1.5 m / s, the quick-setting sheet has a thickness of 0.25-0.4 mm, and the copper roller cooling water temperature is 18-25° C.
7. The preparation method according to claim 5, characterized in that: The hydrogen absorption and dehydrogenation reaction method in step (3) is: breaking the hydrogen tank to evacuate, absorbing hydrogen at room temperature at a hydrogen pressure of 0.5-0.7 MPa for 1.2-2.0 hours, and dehydrogenating at 480-520°C for 2.5-3.5 hours.
8. The preparation method as claimed in claim 5, characterized in that: In the jet milling process in step (4), the rotation speed of the classifying wheel is 4300-4500 r / min.
Citation Information
Patent Citations
Double-hard magnetic main phase mixed rare-earth permanent magnet and preparation method thereof
CN106128674A
Nano double main phase magnet and preparation method thereof
CN109346258A
Preparation method of high-performance multi-main-phase Ce-based nanocrystalline magnet
CN110246644A
W-containing r-fe-b-cu sintered magnet and quenching alloy
WO2015149685A1
High-performance sintered neodymium-iron-boron magnet and preparation method therefor
WO2023001189A1